THE PAST MEETS THE FUTURE – A MUSEUM AS A SMART BUILDING - Dechnik, Mirosław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
This article presents the characteristics of Smart Building technology in the context of their implementation in a museum building. The role of integrated building automation and a control system in an intelligent museum building, its functions, and the issue of maximizing energy efficiency, while ensuring the optimal conditions for preservation of relics, as well as people comfort were presented.